Adverse neuropsychiatric effects of antimalarial drugs. Issue 7 (2nd July 2016) - Grabias, Bryan; Kumar, Sanjai
ABSTRACT: Introduction : Antimalarial drugs are the primary weapon to treat parasite infection, save lives, and curtail further transmission. Accumulating data have indicated that at least some antimalarial drugs may contribute to severe neurological and/or psychiatric side effects which further complicates their use and limits the pool of available medications. Areas covered : In this review article, we summarize published scientific studies in search of evidence of the neuropsychiatric effects that may be attributed to the commonly used antimalarial drugs administered alone or in combination. Each individual drug was used as a search term in addition to keywords such as neuropsychiatric, adverse events, and neurotoxicity. Expert opinion : Accumulating data based on published reports over several decades have suggested that among the major commonly used antimalarial drugs, only mefloquine exhibited clear indications of serious neurological and/or psychiatric side effects. A more systematic approach to assess the neuropsychiatric adverse effects of new or repurposed antimalarial drugs on their safety, tolerability and efficacy phases of clinical studies and in post-marketing surveillance, is needed to ensure that these life-saving tools remain available and can be prescribed with appropriate caution and medical judgment.